2008
DOI: 10.3354/cr00731
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of extreme weather events by a stochastic weather generator

Abstract: A stochastic weather generator is a model capable of generating daily weather patterns that are statistically similar to the observed patterns. Weather generators are commonly used in climate change studies as a computationally inexpensive tool to generate high resolution climate change scenarios based on the output from global climate models. Considering that the frequency and the magnitude of extreme weather events are likely to increase under climate change, there is a growing need to investigate how well w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
159
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(161 citation statements)
references
References 40 publications
0
159
0
2
Order By: Relevance
“…Specifically, climate change scenarios are frequently produced by stochastic weather generators (e.g. Semenov 2008). Conventional weather generators are based on autoregressive-type models for time series of daily minimum and maximum temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, climate change scenarios are frequently produced by stochastic weather generators (e.g. Semenov 2008). Conventional weather generators are based on autoregressive-type models for time series of daily minimum and maximum temperature.…”
Section: Discussionmentioning
confidence: 99%
“…We used the LARS-WG stochastic weather generator (Semenov 2008) to generate three synthetic weather records. These records represented temperature conditions observed at Saiq between 1979 and 2008, as well as two climate change scenarios, in which mean monthly minimum and maximum temperatures were elevated by 1 • C and 2 • C, respectively.…”
Section: Present and Future Chilling Scenariosmentioning
confidence: 99%
“…Several studies [6,[28][29][30][31][32][33] reported that the LARS-WG model was effective in downscaling GCMs outputs. Several studies have reported that the LARS-WG model fits observed air temperature (Tmin and Tmax) [7,23] very well, while its performance in predicting rainfall was reasonable [6].…”
Section: Introductionmentioning
confidence: 99%